Mechanisms of triplet energy transfer across the inorganic nanocrystal/organic molecule interface - Xiao Luo (Nature Portfolio, 2020)
Though literature reports models describing triplet energy transfer between inorganic semiconductors and organic molecules, a unified mechanism for this process is still lacking. Here, the authors report triplet energy transfer mechanism at lead halide perovskite nanocrystal/polyacene interfaces.